Simulating an intra-fraction adaptive workflow to enable PTV margin reduction in MRIgART volumetric modulated arc therapy for prostate SBRT - Snyder, Jeffrey; Smith, Blake; Aubin, Joel St.; Shepard, Andrew; Hyer, Daniel (Frontiers in Oncology, 2024)
Purpose This study simulates a novel prostate SBRT intra-fraction re-optimization workflow in MRIgART to account for prostate intra-fraction motion and evaluates the dosimetric benefit of reducing PTV margins. Materials and methods VMAT prostate SBRT treatment plans were created for 10 patients using two different PTV margins, one with a 5 mm margin except 3 mm posteriorly (standard) and another using uniform 2 mm margins (reduced). All plans were prescribed to 36.25 Gy in 5 fractions and adapted onto each daily MRI dataset. An intra-fraction adaptive workflow was simulated for the reduced margin group by synchronizing the radiation delivery with target position from cine MRI imaging. Intra-fraction delivered dose was reconstructed and prostate DVH metrics were evaluated under three conditions for the reduced margin plans: Without motion compensation (no-adapt), with a single adapt prior to treatment (ATP), and lastly for intra-fraction re-optimization during delivery (intra). Bladder and rectum DVH metrics were compared between the standard and reduced margin plans. Results As expected, rectum V18 Gy was reduced by 4.4 ± 3.9%, D1cc was reduced by 12.2 ± 6.8% (3.4 ± 2.3 Gy), while bladder reductions were 7.8 ± 5.6% for V18 Gy, and 9.6 ± 7.3% (3.4 ± 2.5 Gy) for D1cc for the reduced margin reference plans compared to the standard PTV margin. For the intrafraction replanning approach, average intra-fraction optimization times were 40.0 ± 2.9 seconds, less than the time to deliver one of the four VMAT arcs (104.4 ± 9.3 seconds) used for treatment delivery. When accounting for intra-fraction motion, prostate V36.25 Gy was on average 96.5 ± 4.0%, 99.1 ± 1.3%, and 99.6 ± 0.4 for the non-adapt, ATP, and intra-adapt groups, respectively. The minimum dose received by the prostate was less than 95% of the prescription dose in 84%, 36%, and 10% of fractions, for the non-adapt, ATP, and intra-adapt groups, respectively. Conclusions Intra-fraction re-optimization improves prostate coverage, specifically the minimum dose to the prostate, and enables PTV margin reduction and subsequent OAR sparing. Fast re-optimizations enable uninterrupted treatment delivery.